The effect of bulldozer noise on hearing - NP, Nataraja; G, Subramanya (Journal of All India Institute of Speech and Hearing)
Effect of noise on hearing either in terms of T. T. S. or P. T. S. has been a subject of interest of many people. A number of studies have been conducted to study this phenomenon, around the country and around the world (Larsen, 1939; Rosenblith, 1942; Me Coy, 1944; Urposurala and Eniolahikainen, 1948; Kryter, K. D., 1950 and 1963; Coldner., 1953; Cox, Mansur and Williams, 1953; ASA, 1954; Gangoli and Prakash Rao, 1954; Lindquist, S. E., Neff, W. D., and H. F. Schuknecht, 1954; USAI, 1954; Webster, 1954; Adiseshaiah, et al, 1959; Ward, W. D., A. Glorig, and D. L. Skian, 1959; R. E. Fleer and A. Glorig, 1961; Gallo, R. and A. Glorig, 1964; Mahananda, P., 1972). This may be the first report on effect of bulldozer noise on hearing